Strategi Komunikasi Dakwah Melalui Konten Humor Pada Akun Instagram @memeislam.id - Ach. Atikul Ansori (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2026)
The Instagram account @memeislam.id is one of the digital da’wah media that utilizes humorous content in the form of memes to deliver Islamic messages to a wider audience. This phenomenon shows that social media is not only used for entertainment but also serves as a space for spreading Islamic values in a creative and easily accepted way. This study aims to analyze the communication strategy of da’wah through humorous content and to identify the meaning of da’wah messages contained in memes on the @memeislam.id account. The method used is qualitative with a literature review approach and semiotic analysis based on Ferdinand de Saussure’s theory, which emphasizes the relationship between the signifier and the signified. The results show that meme content on the account contains da’wah messages covering aspects of aqidah (faith), sharia (Islamic law), and akhlaq (morality). In addition, the communication strategy through humor-based personal branding is effective in increasing message reach and gaining positive responses from social media users. Keywords: digital da’wah; meme; semiotics; personal branding